2016
DOI: 10.1039/c6an00158k
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in chromogenic and fluorogenic chemosensors for hypochlorous acid

Abstract: Due to the biological and industrial importance of hypochlorous acid, the development of optical probes for HOCl has been an active research area. Hypochlorous acid and hypochlorite can oxidize electron-rich analytes with accompanying changes in molecular sensor spectroscopic profiles. Probes for such processes may monitor HOCl levels in the environment or in an organism and via bio-labeling or bioimaging techniques. This review summarizes recent developments in the area of chromogenic and fluorogenic chemosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(69 citation statements)
references
References 69 publications
1
63
0
4
Order By: Relevance
“…It is now apparent that the previously reported decrease in fluorescence intensity during Cl À oxidation was likely due to fluorescence quenching and not to desalination. [55] We conclude that electrochemical Cl À oxidation does not form a significant IDZ or electric field gradient in solution that can be used for saltwater desalination. Furthermore, these findings demonstrate that undesired (or unknown) electrochemical and chemical processes can prevent formation of an IDZ and electric field gradient in other electrochemical systems.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is now apparent that the previously reported decrease in fluorescence intensity during Cl À oxidation was likely due to fluorescence quenching and not to desalination. [55] We conclude that electrochemical Cl À oxidation does not form a significant IDZ or electric field gradient in solution that can be used for saltwater desalination. Furthermore, these findings demonstrate that undesired (or unknown) electrochemical and chemical processes can prevent formation of an IDZ and electric field gradient in other electrochemical systems.…”
Section: Discussionmentioning
confidence: 80%
“…Second, the ECP gradient measured during electrochemical Cl − oxidation is caused by a shift in the chemical potential, rather than the electric potential, of the solution in the vicinity of the anode. It is now apparent that the previously reported decrease in fluorescence intensity during Cl − oxidation was likely due to fluorescence quenching and not to desalination …”
Section: Discussionmentioning
confidence: 89%
“…Recently studies revealed that this molecule is an important microbicidal agent during immune inflammation response, corresponding to the digestion of the bacterium engulfed by neutrophil phagosome . However, overbalance of HOCl production during inflammation is implicated with many diseases, including Alzheimer disease, cardiovascular disease, atherosclerosis, ischemia‐reperfusion injury in stroke, osteoarthritis, inflammatory bowel disease, myocardial infarction, organ transplant rejection, and even cancers …”
Section: Introductionmentioning
confidence: 98%
“…However, more than 100 reports have been published in the literature regarding this single analyte (Scheme ). There is still room to develop an excellent probe for detection of this ROS; importantly, R. Strongin and co‐workers reported the first review article which covered the recent progress in chromogenic and fluorogenic chemosensors for HOCl (2016) . Recently, the D. Yang group has reported coverage for the fluorescent probes for HOCl imaging .…”
Section: Introductionmentioning
confidence: 99%
“…There is still room to develop an excellent probe for detection of this ROS;importantly,R.Strongin and co-workersr eported the first review article which covered the recent progress in chromogenic and fluorogenic chemosensors forH OCl (2016). [18] Recently,t he D. Yang group has reported coverage for the fluorescent probes for HOCl imaging. [19] In both earlier reports, the authorsh ad not covered extensively all reports of HOCl detection.…”
Section: Introductionmentioning
confidence: 99%